Improving adherence to and effectiveness of a vancomycin continuous infusion protocol, a pilot quality improvement project. (30th November 2022) - Oakley, R; Trinh, H; Yau, T; Khorshid, S; Lonsdale, D
Abstract: Introduction: Vancomycin treats serious Gram-positive infections such as methicillin-resistant Staphylococcus aureus . In St George's University Hospital's (SGH) intensive care unit (ICU) settings, vancomycin is administered by continuous infusion. Steady-state serum concentrations are measured daily with a 20-25 mg/L target. Non-therapeutic concentrations are associated with adverse drug reactions/prolonged length of stay. 1 A SGH service-evaluation conducted across all three ICUs, revealed variable adherence to/effectiveness of its vancomycin prescribing/administration/monitoring protocol. 2 Consequently, multifaceted interventions were devised using the Institute-for-Healthcare-Improvement's model Plan-Do-Study-Act (PDSA) cycles and piloted on General ICU (GICU). Aim: (1) To improve adherence to/effectiveness of the vancomycin protocol. (2) To ascertain administration accuracy of paper-fluid-balance-charts compared to the electronic-prescribing-and-medicines-administration (ePMA) system to assist with identifying per protocol treated patients. Methods: PDSA Cycle-1 was conducted over a 9-month period (09/2021-05/2021) in which a mix of system/person-focused interventions were implemented. Protocol dosing 2 was revised, introducing a >90kg patient 2g loading dose, renal-function category revision and increased maintenance dose for creatinine clearance (CLCR ) >90ml/min. Protocol accessibility was increased via integration into an ePMA prescribing interface, plus CliniBee/Microguide apps. Educational slides on relevant protocol aspects were incorporated into medical/nursing induction training. Data relating to vancomycin prescribing/administration/monitoring for all non-renal replacement patients was extracted retrospectively from the ePMA system between 09/2021-05/2022. This data was compared to baseline GICU data (07/2020-07/2021). 2 The project and associated interventions were approved by Trust Clinical Governance and Audit Teams. Data was collected by pharmacists directly involved in patient's care and stored/analysed on the Trust's secure server in line with Data Protection Act principles. Due to local generalisability, ethics approval wasn't required. Results: Compared to baseline, the proportion of patients receiving per protocol prescribing/administration of loading/maintenance doses with daily monitoring, nearly doubled (39% (7/18) to 68% (15/22)). 48-hour vancomycin serum concentrations in all patients increased therapeutically by 21% (3/9 to 7/13). In per protocol treated patients, concentrations increased 15% (2/7 to 4/9) therapeutically, decreased 21% (3/7 to 2/9) supra-therapeutically and increased 4% (2/7 to 3/9) sub-therapeutically. Supra-therapeutic concentrations were associated with CLCR <50ml/min. Sub-therapeutic concentrations were associated with CLCR >90ml/min and obesity. Compared to the ePMA system, there was 36% (8/22) less paper-fluid-balance-charts recording both loading/maintenance doses. Maintenance dose administration times in 9% (2/22) of cases differed by >60 minutes. Discussion/Conclusion: Staff-turnover periods were associated with decreased protocol compliance. Observations suggest further education is required around prescribing/administration of standardised infusion bags for maintenance dosing. Pharmacist integration into daily Microbiology ward rounds may increase protocol compliance. Higher 20mg/kg loading doses for obese patients and maintenance dose revision should be considered to reduce non-therapeutic concentrations. 3 Limitations include heterogenous/small sample sizes due to data paucity and vancomycin requirement. This can be addressed by involving all ICU's in PDSA Cycle-2. Due to disparities, both the ePMA system and paper-fluid-balance-charts should be used to identify protocol adherence. Utilisation of digital-infusion-pump data to quantify administration accuracy may offer a promising solution. Piloted multifaceted interventions were successful at improving adherence to/effectiveness of the vancomycin protocol. Findings have informed further interventions and data capture methods for PDSA Cycle-2 implementation across all ICUs. References: 1. Perin N, Roger C, Marin G, Molinari N, Evrard A, Lavigne J et al. Vancomycin Serum Concentration after 48 h of Administration: A 3-Years Survey in an Intensive Care Unit. Antibiotics. 2020;9(11):793. Available from: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC7698174/ 2. Oakley R, Bakrania P, Yau T, Standing J, Lonsdale D. P37 Variable adherence to and effectiveness of a vancomycin continuous infusion protocol within ICUs at a London tertiary-care hospital: a single-centre retrospective service evaluation. JAC-Antimicrobial Resistance. 2022;4(Supplement_1). Available from: https://academic.oup.com/jacamr/issue/4/Supplement_1 3. Rybak M, Le J, Lodise T, Levine D, Bradley J, Liu C et al. Therapeutic monitoring of vancomycin for serious methicillin-resistant Staphylococcus aureus infections: A revised consensus guideline and review by the American Society of Health-System Pharmacists, the Infectious Diseases Society of America, the Pediatric Infectious Diseases Society, and the Society of Infectious Diseases Pharmacists. American Journal of Health-System Pharmacy. 2020;77(11):835-864. Available from: https://academic.oup.com/ajhp/article/77/11/835/5810200?login=false